Perspectives of two college students labeled with intellectual disability: Supports during the moving in and through stages of transition - Amanda L. Miller; Mina Chun (Disability Studies Quarterly, 2022)
An increasing number of students labeled with intellectual disability are attending colleges and universities. Yet, their perspectives are underrepresented in the research. Grounded in Disability Studies in Education and Schlossberg's Transition Theory, this study reports on the transitional experiences of two emerging adults labeled with intellectual disability at a large public university with a particular focus on how the participants conceptualized their support systems during the moving in and through stages of transition to university. Three themes are discussed: supports the students brought with them to the university, reciprocal supports with peer mentors, and university-provided supports. As such, the findings contribute to and expand existing scholarship dedicated to the experiences of emerging adults labeled with intellectual disability at postsecondary institutions. Aligning with the research question and blended theoretical framing, implications for practice and research are discussed.